A nurse‐driven process for timely removal of urinary catheters. Issue 3 (4th April 2016) - Yatim, Juriyah; Wong, Kok‐Seng; Ling, Moi‐Lin; Tan, Siok‐Bee; Tan, Kwee‐Yuen; Hockenberry, Marilyn
ABSTRACT: Catheter‐associated urinary tract infection (CAUTI) comprises 30–40% of all health care‐acquired infections, and 70–80% of these infections are related with use of indwelling urinary catheters. This quality improvement (QI) project was initiated to evaluate the effectiveness of a nurse‐driven urinary catheter removal process in reducing the duration of urinary catheter usage in a general medical ward in Singapore. A pre‐ and post‐study design was adopted. The pre‐implementation data included urinary catheter utilization ratio and CAUTI rates. Over a 6‐months period, nurses used a nurse‐driven urinary catheter removal process to improve rates of timely removal of catheter. Data collected included nurses' compliance with the process and clinical outcomes, such as urinary catheter utilization ratio and CAUTI rates before and after implementation. Compliance with the use of the nurse‐driven process by staff was 89%. The urinary catheter utilization ratio revealed a raise from 0·12 before implementation to 0·18 after implementation. However, CAUTI rates decreased from 4 to 0 per 1000 catheter‐days, indicating a marginally significant difference between the pre and post‐implementation rates ( p = 0.06), using Fisher's exact test. The nurse‐driven process decision support tool for optimizing appropriate catheter usage had the potential of reducing a patient's risk of acquiring CAUTI.